FEATURES OF DIGITALIZATION OF THE BANKING STRUCTURE IN THE CONTEXT OF GLOBALIZATION (Conferencea, 2022)
The object of the study is banking credit organizations operating with the use of new information technologies. The subject is digital banking technologies. The methodological base was made up of a systematic approach in the field of analysis of the functioning of banking credit organizations; method of comparative analysis, on the basis of which the performance indicators of banking credit organizations are interpreted; a method of dynamic analysis that made it possible to identify the main trends in the development of the banking sector. The goal is, based on the generalization of the collected data, to determine the main trends in the digitalization of the banking sector and the risks associated with it. The activities of credit institutions are undergoing a stage of digital transformation and the introduction of new technologies. Innovations in the banking business are associated with the emergence of electronic money and the gradual transition to settlement with it, the use of an electronic digital signature, contactless payments, the use of blockchain technologies, the Internet of things. The usual approaches to customer service are being replaced by best practices, and a gradual transformation of a traditional bank into a multifunctional IT company is taking place. This transformation involves the growth of threats in the field of information security, requires the improvement of approaches to managing the relevant risks in the bank's activities.